Conceptual Exploration of the Appointment of Murshid in Tarekat Qadiriyah Naqsyabandiyah Suryalaya Islamic Boarding School with a Da'wah Communication Approach - Marzuqi, Muhammad Ganda; Nurdin, Ali (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
One of the important roles in the Islamization process in the archipelago is the tariqat. Tarekat is literally a